2021
DOI: 10.1111/cogs.13046
|View full text |Cite
|
Sign up to set email alerts
|

Discerning Mouse Trajectory Features With the Drift Diffusion Model

Abstract: Mouse tracking, a new action-based measure of behavior, has advanced theories of decision making with the notion that cognitive and social decision making is fundamentally dynamic. Implicit in this theory is that people's decision strategies, such as discounting delayed rewards, are stable over task design and that mouse trajectory features correspond to specific segments of decision making. By applying the hierarchical drift diffusion model and the Bayesian delay discounting model, we tested these assumptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…We computed conflict-strength measures for each of the trajectories: (a) Maximum Deviation (MD; Boschet et al, 2022; Cummins & De Houwer, 2021; Dale & Duran, 2011; Freeman, 2014; Freeman & Ambady, 2009; Freeman et al, 2008; Garcia-Guerrero et al, 2023; Maldonado et al, 2019; McKinstry et al, 2008; Stillman et al, 2017)—the largest perpendicular deviation of the actual trajectory from an ideal straight line between the start and end points, and (b) Area under the Curve (AUC; Boschet et al, 2022; Cummins & De Houwer, 2021; Dale et al, 2007; Freeman & Ambady, 2010; Garcia-Guerrero et al, 2023; Leontyev & Yamauchi, 2021; Spivey et al, 2005; Stillman et al, 2017, 2020)—the geometric area between the actual trajectory and an ideal line. We further computed two measures corresponding to the mechanistic properties of the force-fields theory: (c) x-flips (to measure oscillatory behavior; Dale & Duran, 2011; Dale et al, 2008; Freeman, 2014; Freeman & Ambady, 2010; Freeman & Johnson, 2016)—the number of reversals of direction along the x -axis, and (d) Returns to Point of Balance (RPB; to quantify the extent to which participants were stuck in the middle between the options in a given trial)—the number of returns to the line where the x coordinate equals 0 (Koop & Johnson, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…We computed conflict-strength measures for each of the trajectories: (a) Maximum Deviation (MD; Boschet et al, 2022; Cummins & De Houwer, 2021; Dale & Duran, 2011; Freeman, 2014; Freeman & Ambady, 2009; Freeman et al, 2008; Garcia-Guerrero et al, 2023; Maldonado et al, 2019; McKinstry et al, 2008; Stillman et al, 2017)—the largest perpendicular deviation of the actual trajectory from an ideal straight line between the start and end points, and (b) Area under the Curve (AUC; Boschet et al, 2022; Cummins & De Houwer, 2021; Dale et al, 2007; Freeman & Ambady, 2010; Garcia-Guerrero et al, 2023; Leontyev & Yamauchi, 2021; Spivey et al, 2005; Stillman et al, 2017, 2020)—the geometric area between the actual trajectory and an ideal line. We further computed two measures corresponding to the mechanistic properties of the force-fields theory: (c) x-flips (to measure oscillatory behavior; Dale & Duran, 2011; Dale et al, 2008; Freeman, 2014; Freeman & Ambady, 2010; Freeman & Johnson, 2016)—the number of reversals of direction along the x -axis, and (d) Returns to Point of Balance (RPB; to quantify the extent to which participants were stuck in the middle between the options in a given trial)—the number of returns to the line where the x coordinate equals 0 (Koop & Johnson, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies indicated that the area under the curve (AUC) of mouse cursor movements can be used as an index of the extent of cognitive conflicts [30][31][32] . The AUC is defined as the amount of area between the actual trajectory and a straight trajectory from trial onset to response termination (Figure 4; e.g., 33 ).…”
Section: Measurements Of Thinking Costs (Cognitive Conflicts and Subj...mentioning
confidence: 99%
“…Maximum velocity time. Maximum velocity time is defined as the time at which the maximum velocity of a mouse movement is achieved in a trial (e.g., 25,39,40). People are expected to move a mouse quickly when they judge which alternatives to choose in their minds.…”
Section: General Information (Common To All Groups)mentioning
confidence: 99%